2018
DOI: 10.1016/j.neuroscience.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive PGC-1α Overexpression in Skeletal Muscle Does Not Improve Morphological Outcome in Mouse Models of Brain Irradiation or Cortical Stroke

Abstract: Physical exercise can improve morphological outcomes after ischemic stroke and ameliorate irradiation-induced reduction of hippocampal neurogenesis in rodents, but the mechanisms underlying these effects remain largely unknown. The transcription factor peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) is considered to be one of the central factors responsible for exercise-induced benefits in skeletal muscle, including the release of neurotrophic factors into the circulation. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 306 publications
2
16
1
Order By: Relevance
“…The transgenic mouse model used in this study has a moderate overexpression of PGC-1α and its downstream effector genes Fndc5, Vegfb, IL15, Timp4, and Ctsb [34,35] and displays an endurance muscle phenotype with high mitochondrial density [34]. In this study, we observed a 3-4-fold increase in PGC-1α protein expression in gastrocnemius of transgenic sedentary female and male animals.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The transgenic mouse model used in this study has a moderate overexpression of PGC-1α and its downstream effector genes Fndc5, Vegfb, IL15, Timp4, and Ctsb [34,35] and displays an endurance muscle phenotype with high mitochondrial density [34]. In this study, we observed a 3-4-fold increase in PGC-1α protein expression in gastrocnemius of transgenic sedentary female and male animals.…”
Section: Discussionsupporting
confidence: 49%
“…In particular, we studied effects of exercise, aging and genotype on hippocampal neurogenesis. The MCK-PGC-1α mouse model used in this study has previously been validated by us to have a developed endurance muscle phenotype [34,35]. Western blot on gastrocnemius homogenate of middle-aged (7-10-month-old) sedentary animals show that MCK-PGC-1α animals have around 4-fold increased PGC-1α levels in comparison to wild-type animals (t test with Welch correction, n = 3, p = 0.043; all female animals except for one male individual in WT sedentary; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…008231), a kind gift from Dr. Bruce Spiegelman (Harvard Medical School, Boston, MA), have been previously described 9 . Housing and breeding conditions have been described previously 31 . All experiments were approved by the Gothenburg ethical committee on animal research (#317-2012 and #181-2015) and were performed in accordance with relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…The statistical significance of the observed difference in western blot analysis was determined by parametric (Welch's t) or non-parametric (Mann-Whitney test) tests when data failed the Shapiro-Wilk normality test. Mass spectrometry data (LF) statistical significance was determined by the unpaired Student's t-test and differences were considered statistically significant at Benjamini-Hochberg corrected p-value (FDR)<0.05 [44].…”
Section: Statistical Analysesmentioning
confidence: 99%